IMPLEMENTASI KEBIJAKAN PAJAK DAERAH DI KABUPATEN PELALAWAN (Studi Kasus Pada Pajak Sarang Burung Walet) - Sarlis Sarlis; Hasim As’ari (Journal Publicuho, 2021)
Swallow's nest tax collection is targeted to break the local revenue of Pelalawan Regency every year and the breeding or exploitation of swiftlet nests can be one of the new potentials that can improve people's living standards through local regulations that regulate it. In carrying out the collection of swallow nest taxes, regulations are issued by the government in the form of Pelalawan Regency Regional Regulation No. 1 of 2011 concerning Regional Taxes. The purpose of this study was to determine the implementation of local tax policies in Pelalawan Regency, especially the swallow's nest tax and to identify the inhibiting factors for the implementation of local tax policies in Pelalawan Regency, especially the swallow's nest tax. To achieve this goal, this research uses interactive analysis techniques with qualitative research types using a descriptive approach and the required data, both primary and secondary data obtained through interviews and documentation, are then analyzed based on research problems. This study shows that first, the implementation of local tax policies in Pelalawan Regency (a case study on the swiftlet nest tax) has not been implemented properly, which can be seen from three indicators, namely the mentality approach, the systems approach and the network cooperation approach. Second, the inhibiting factors are the absence of a license, it is difficult to find the owner of the swallow, there are incorrect issues about taxes, and the government's indecisiveness.